Tourism Attractions and Their Influence on the Sustainable Green Economy: A Study of Amenities, Accessibility, and Policy Network - Raden Galih Teja Gumilang; Sakir Sakir; Fairuz Arta Abhipraya (Mitra Edukasi dan Publikasi, 2026)
Tourism villages play a crucial role in promoting sustainable regional development by integrating environmental preservation with local economic empowerment. In this context, Senaru Tourism Village represents a model of how natural and cultural attractions can contribute to a sustainable green economy. The purpose of this study is to find out the Influence of Senaru Village Tourism Attraction on the Sustainable Green Economy. The research method used was quantitative, with the primary data source being a questionnaire of 200 respondents (domestic and foreign tourists). The selection of Senaru Tourism Village with a policy network approach, the development of Senaru Village is no longer only oriented towards increasing the number of tourist visits, but shifting towards fulfilling overall welfare or destination tourism wellbeing (DTW). Measurement is carried out using variables from the tourist attraction framework consisting of amenities, attractions, accessibility, and other supporting factors. The research method used was quantitative, with the primary data source being a questionnaire of 200 respondents (domestic and foreign tourists). Data analysis using SEM-pls software was used in conducting data analysis for this study. Data presentation used the results of hypothesis tests, Cronbach alpha, and statistical t-values. The results of the study show that three of the five variables which include amenities, accessibility, and Policy Network have an effect on the green economy. Then for the attraction and ancillary variables have no effect on the green economy.